2021
DOI: 10.1002/jrs.6168
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman study of cesanite (Ca2Na3 (OH)(SO4)3) in chloride segregations from Udachnaya‐East kimberlites

Abstract: Cesanite (Ca2Na3(OH)(SO4)3), a rare mineral, has been found in a few places restricted to a geothermal field and caves. We report the new occurrence of cesanite in quite different geological site—within sulfate‐rich melt inclusions in chloride segregations from kimberlites of Udachnaya‐East pipe (Siberia). Two halite generations: сesanite free and сesanite‐bearing, were distinguished in concentrically zonal segregations according to the results of the mineral and sulfate melt inclusion study by micro‐Raman spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…[51] The sharp band at 990 cm À 1 in the infrared spectrum and very strong band in the Raman spectrum at 994 cm À 1 are representing symmetric stretching modes of the SO 4 tetrahedra. [52] Bands related to asymmetric bending modes observed in the region of 550-680 cm À 1 in the infrared spectrum are in the range of 590-660 cm À 1 in the Raman spectrum. Raman bands between 420 and 480 cm À 1 are symmetric bending vibrations of sulfate ions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[51] The sharp band at 990 cm À 1 in the infrared spectrum and very strong band in the Raman spectrum at 994 cm À 1 are representing symmetric stretching modes of the SO 4 tetrahedra. [52] Bands related to asymmetric bending modes observed in the region of 550-680 cm À 1 in the infrared spectrum are in the range of 590-660 cm À 1 in the Raman spectrum. Raman bands between 420 and 480 cm À 1 are symmetric bending vibrations of sulfate ions.…”
Section: Resultsmentioning
confidence: 95%
“…Broad bands related to asymmetric stretching vibrations of [SO 4 ] 2− ions observed in the regions of 1025–1250 cm −1 [51] . The sharp band at 990 cm −1 in the infrared spectrum and very strong band in the Raman spectrum at 994 cm −1 are representing symmetric stretching modes of the SO 4 tetrahedra [52] . Bands related to asymmetric bending modes observed in the region of 550–680 cm −1 in the infrared spectrum are in the range of 590–660 cm −1 in the Raman spectrum.…”
Section: Resultsmentioning
confidence: 96%
“…The spectra shown in Figure 2 are the average of between 9 and 13 individual spectra for each sample. The region of the Raman spectra exhibiting stretching modes of water from 3000 to 3800 cm −1 (e.g., Shahar & Bassett 2005;Kolesov 2006;de Ligny et al 2013;Grishina et al 2021) displays a complex profile of overlapping bands in all three samples. The five bands at 3066, 3194, 3306, 3400, and 3510 cm −1 used to fit the spectra are consistent with analogous molecular water features observed in other water-bearing minerals, like those in kimberlite inclusions (e.g., Grishina et al 2021).…”
Section: Resultsmentioning
confidence: 96%
“…The local baselines were fit with linear functions. The region of Raman spectra corresponding to water stretching modes, from 3000 to 3800 cm −1 (e.g., Shahar & Bassett 2005;Kolesov 2006;de Ligny et al 2013;Grishina et al 2021), was fit using Lorentzian line shapes (Bancroft et al 2018). Five bands of molecular water at 3066, 3194, 3306, 3400, and 3510 cm −1 were used to fit the spectra.…”
Section: mentioning
confidence: 99%
“…Grishina et al [ 13 ] reported the new occurrence of cesanite in quite different geological site within sulfate‐rich melt inclusions in chloride segregations from kimberlites of Udachnaya‐East pipe (Siberia). Cesanite (Ca 2 Na 3 (OH)(SO 4 ) 3 ) is a rare mineral found in a few places restricted to a geothermal field and caves.…”
Section: Mineralogy Petrology and Volcanology A Place Of Opportunitie...mentioning
confidence: 99%